Vegetarianism and meat consumption: A comparison of attitudes and beliefs between vegetarian, semi-vegetarian, and omnivorous subjects in Belgium. (1st July 2017) - Mullee, Amy; Vermeire, Leen; Vanaelst, Barbara; Mullie, Patrick; Deriemaeker, Peter; Leenaert, Tobias; De Henauw, Stefaan; Dunne, Aoibheann; Gunter, Marc J.; Clarys, Peter; Huybrechts, Inge
Abstract: High levels of meat consumption in Belgium may be contributing to increased risk of non-communicable diseases in this population. The objective of this study is to investigate the attitudes and beliefs about vegetarianism and meat consumption among the Belgian population, ultimately to better understand the motivations underlying these dietary behaviours. This cross-sectional study was initiated in March 2011. A total of 2436 individuals from a representative consumer panel from the Flemish and Brussels communities participated. The study sample was evenly distributed by education level and sex (1238 men and 1198 women). An online questionnaire with multiple-choice questions about vegetarianism and meat consumption was completed by all participants. Although representative of the prevalence of vegetarians in the population, the number of vegetarians in the study was low (n = 38); the number of semi-vegetarians (n = 288) and omnivores was high (n = 2031). Vegetarians were more likely than semi-vegetarians to agree that meat production is bad for the environment and that meat consumption is unhealthy. Important reasons for not being vegetarian included lack of interest and awareness, taste, and limited cooking skills. Encouragingly, health and discovering new tastes were seen as the most important motives for considering eating a more vegetarian-based diet. The results of this study highlight the motivations that can be used for encouraging the general public to reduce their meat consumption in favour of a plant-rich diet, and will help to inform more targeted health campaigns for reducing meat consumption in Belgium.